2013
DOI: 10.1021/ol402561q
|View full text |Cite
|
Sign up to set email alerts
|

Stereocontrol in Asymmetric γ-Lactam Syntheses from Imines and Cyanosuccinic Anhydrides

Abstract: Computations (SCS-MP2//B3LYP) reveal that the asymmetric synthesis of highly substituted γ-lactams with three stereogenic centers, including one quaternary center, proceeds through a Mannich reaction between the enol form of the anhydride and the E-imine, followed by a transannular acylation. This new mechanistic picture accounts for both the observed reactivity and stereoselectivity. CH-O and hydrogen bonding interactions in the Mannich step and torsional steering effects in the acylation step are responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…Nucleophilic addition of the imine nitrogen acting as a nucleophile toward the (less reactive) C-1 carbonyl of HPA or its enol tautomer has been proposed, 2,22 but more recently, calculations have been reported that suggest that this pathway is too high in energy. 23 Concerted cycloaddition of imine with a diene-like enol of HPA ( 13 ) or its derived enolate have been considered, 24,25 but imines are normally regarded as weak dienophiles in a thermal Diels-Alder reaction, 26 and 1 reacts rapidly with 2 even at mild temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleophilic addition of the imine nitrogen acting as a nucleophile toward the (less reactive) C-1 carbonyl of HPA or its enol tautomer has been proposed, 2,22 but more recently, calculations have been reported that suggest that this pathway is too high in energy. 23 Concerted cycloaddition of imine with a diene-like enol of HPA ( 13 ) or its derived enolate have been considered, 24,25 but imines are normally regarded as weak dienophiles in a thermal Diels-Alder reaction, 26 and 1 reacts rapidly with 2 even at mild temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…A concerted, cyclic, Mannich-like reaction 23 of the enol of HPA ( 13 ) accounts for the reactivity of imine 2 despite its low basicity and nucleophilicity (Scheme 5). A hydrogen bond between enol 13 as the donor and the imine nitrogen of 2 as the acceptor can organize the two coupling partners into a transition state geometry in which either the N -2,2,2-trifluoroethyl substituent of 2 lies over the HPA ring oxygen (a “boat”, 14 ), or the pyridine ring of 2 lies over the HPA C-1 carbonyl group (a “chair”, 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Organization of the reaction components 2 and 3 by an intermolecular hydrogen bond 13,22 could take place in two different configurations (Scheme 2). The “boat” configuration ( 7 ) places the aryl group away from the benzo ring, and ought to be favored for small N-substituents R .…”
Section: Resultsmentioning
confidence: 99%
“…Despite earlier considerations of alternative mechanisms, 2,14,21 more recent analysis of the HPA-imine reaction seems to have settled on a two-step process centered on Mannich-type amino-anhydride intermediate 5 , 3,13,15,22 the stereochemistry of which translates to the C-3 and C-4 stereocenters of the THIQ product. Under certain conditions, elimination of amine from 5 to afford a Knoevenagel-type alkene product 6 has been observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation